Food-Energy-Water Nexus Resilience and Sustainable Development Decision-Making Methods, Planning, and Trade-Off Analysis - Asadi, Somayeh; Mohammadi-Ivatloo, Behnam (Springer International Publishing : Imprint: Springer, 2020)
X, 358 p. 136 illus., 120 illus. in color.